The Basic Emotions of Disadvantaged Immigrant Subjects: A Case Study - Liberato, Ana S.Q.; Justus Liebig University Giessen (My University, 2021)
This sociological study analyzes the emotions of Dominican immigrants in Switzerland when they interact with the majority group. Respondents emphasized feeling disrespected, mistreated, minimized, ignored, unwelcomed, rejected, and misrepresented. They talked about pain, indignation, feeling like an outsider and a lot of pressure to conform to Swiss culture. They also underlined resiliency, courage, national pride, confidence and power over the assumed currency of their physical and sexual appeal. The study shows that power-status inequalities and racist structures produce negative emotions, but some immigrants can manage them through alternative appraisals and redirecting blame. National identity, cultural aspects, transnational knowledge, gender and sexual meanings matter in their appraisals. There is an emotional advantage for those who feel more culturally integrated. More research is needed to shed light on the emotionally of majority-minority interactions, particularly the strategies adopted by disadvantaged immigrants in managing intense emotions within specific life realms.
Keywords: emotions; immigration; power-status theory; Dominican immigrants; Switzerland; ddc:300